Driver’s performance under different secondary tasks and disruptions on rural road environment - Iylia Azura Mohd Mohid; Nor Kamaliana Khamis; Mohd Aizat Shamsuddin; Nurainaa Kabilmahir; Nor Azila Noh (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nowadays, detection of driver’s fatigue is a major concern in vehicle design, road safety and transportation research. Driving tasks requires full attention from the drivers while operating the vehicle. Occasionally, drivers are exposed to perform other activities such as talking to a passenger and using an in-vehicle technology or phone which is known as secondary task while driving. Thus, this study aims to analyse the driver’s performance via three types of physiological measurements in a simulated condition. An integrated approach by combining subjective and objective methods were used in this study. There are Karolinska Sleepiness Scale (KSS), Electroencephalogram (EEG) and Heart Rate (HR). Twelve participants were recruited to evaluate their responses towards different types of secondary tasks and disruptions in 25-minutes of driving duration. The findings showed that there are differences in physiological responses for this driving session. Beta Activity shows higher event-related power modulation values from start until the end of the driving session. In conclusion, the type of disruption during driving and secondary tasks shows different findings towards driver driving performances. This study can be used as reference to drivers and related agencies by taking into account the physiological effects of driver’s performance based on different secondary tasks and disruptions while driving.